Desenvolvimento e produtividade de cultivares de arroz de terras altas em função do manejo do solo - Nascente, Adriano Stephan; Kluthcouski, João; Rabelo, Raimundo Ricardo; de Oliveira, Priscila; Cobucci, Tarcísio; Crusciol, Carlos Alexandre Costa [UNESP] (My University, 2011)
The identification of upland rice cultivars for each kind of soil management system can increase upland rice yield. So, this study aimed to evaluate upland rice genotypes under two soil management systems: conventional tillage (CT) and no-tillage (NT). The experiment was carried out in Ipameri, Goiás State, Brazil, in 2008/2009. A randomized blocks design, in a 2x8 factorial scheme, with sixteen treatments and four replications was used. The first factor was the soil management system (CT and NT) and the second one rice genotypes (BRS Curinga, BRS Primavera, BRS Monarca, BRS Pepita, BRS Sertaneja, Carajás, Caiapó, and Bonança). Plants grew higher under CT than NT. For number of tillers per plant, there were differences among rice cultivars, according to the soil management system. For yield, CT provided higher rates (average of 4,349 kg ha-1) than NT (average of 3,521 kg ha-1), being the number of panicles m-2 and number of grains panicle-1 the yield components responsible for that difference. All cultivars presented statistic differences between the two soil management systems, except for the Caiapó cultivar. For both systems, Carajás reached the highest yield, differing from the BRS Sertaneja and BRS Primavera cultivars.
Upland rice cultivars development and yield regarding soil management
Keywords: Moldboard plow; No-tillage system; Oryza sativa; Yield